National Interest and European Law in the Legislation and Juridical Practice on Health Care Services – In the Light of the Reforms of the Hungarian Health Care System - István Hoffman (Central European Public Administration Review)
The priority of the national interest in the field of the health care policy is secured by the rules of the TFEU, the Charter of Fundamental Rights of the European Union and by the secondary law as well. Although several market-type and pro-competitive solutions have appeared, they can have only limited influence on the national systems. The main reasons of the limited influence of the EU regulations are the primary responsibilities of the Member States, the widely applicable public health exceptions, and the limited application of the EU competition rules. Although the national legislation is the determinative, the EU regulations on the free movement of persons and services could be applied in the field of the health care services. This principle was recognized by the landmark decisions of the Court of Justice (ECJ). The Directive 2011/24/EU is based on these principles and a limited competition has evolved. Because the competition is limited and the creation of a single European health care area has just begun, the “silent revolution” of the public service provision has a minor importance. The practice of the ECJ has been focused on the use of the cross-border services and the Member States have had a broad margin for the organisation and management of this public service. The role of the European legislation on the competition is limited in this field as well. Therefore the strong centralization of the Hungarian health system from 2011 to 2013 may be in harmony with the EU legislation, although the competition at the national level is not promoted by the reformed Hungarian rules on health care.